Differential Roles of PML Isoforms - Nisole, Sébastien; Maroui, Mohamed Ali; Mascle, Xavier; Aubry, Muriel; Chelbi-Alix, Mounira K. (Frontiers in Oncology, 2013)
The tumor suppressor promyelocytic leukemia protein (PML) is fused to the retinoic acid receptor alpha in patients suffering from acute promyelocytic leukemia (APL). Treatment of APL patients with arsenic trioxide (As2O3) reverses the disease phenotype by a process involving the degradation of the fusion protein via its PML moiety. Several PML isoforms are generated from a single PML gene by alternative splicing. They share the same N-terminal region containing the RBCC/TRIM motif but differ in their C-terminal sequences. Recent studies of all the PML isoforms reveal the specific functions of each. Here, we review the nomenclature and structural organization of the PML isoforms in order to clarify the various designations and classifications found in different databases. The functions of the PML isoforms and their differential roles in antiviral defense also are reviewed. Finally, the key players involved in the degradation of the PML isoforms in response to As2O3 or other inducers are discussed.